2020
DOI: 10.21203/rs.3.rs-24562/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude and practices (KAP) towards COVID-19 and assessment of risks of infection by SARS-CoV-2 among the Bangladeshi population: An online cross sectional survey

Abstract: The COVID19 pandemic has been transmitted worldwide rapidly. The best ways of preventing this virus are to know about and act accordingly. An online cross sectional survey was conducted to know the knowledge, attitude and practices towards COVID19 and to assess the risks of infections among Bangladeshi population. Among 2045 respondents, 54·87% respondents kept good knowledge. Knowledge was significantly diverged across age, gender, education levels, residences, income groups, and marital status. Despite the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 2 publications
4
16
1
3
Order By: Relevance
“…This kind of occurrence can force the business to close immediately (SGS, 2020). In another study from Bangladesh by Haque et al, (2020), it was observed that nearly 30% of the participants frequently go outside and meet their friends. On the contrary, many improved practices in avoiding crowds can be seen in different study groups from Malaysia (Azlan et al, 2020), China (Zhong et al, 2020), and Iran (Taghrir et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of occurrence can force the business to close immediately (SGS, 2020). In another study from Bangladesh by Haque et al, (2020), it was observed that nearly 30% of the participants frequently go outside and meet their friends. On the contrary, many improved practices in avoiding crowds can be seen in different study groups from Malaysia (Azlan et al, 2020), China (Zhong et al, 2020), and Iran (Taghrir et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…from diverse occupations [3,9,[19][20][21]. The major strengths of the study are its large sample size and district-wise mapping, which provides a better insight of the scenario towards COVID-19 in Bangladesh.…”
Section: Plos Onementioning
confidence: 99%
“…This can reduce the government's burden in combating the outbreak strategies. There are a few studies [3,9,[19][20][21] that have been conducted in the country which address this issue. However, these studies are nonrepresentative with limited sample sizes and do not provide any (i) district-wise mapping regarding knowledge and preventive behaviors, or (ii) use any models.…”
Section: Introductionmentioning
confidence: 99%
“…Haque ve ark. 'nın (2020) yaptığı çalışmada yaş, cinsiyet, eğitim düzeyi, sosyo-ekonomik durum ve ikamet yerleri gibi etkenlerin COVID-19 bilgi düzeyini önemli ölçüde etkilediği bildirilmiştir (15). Zannatul ve ark.…”
Section: Discussionunclassified
“…COVID-19 hızlı bulaşması, özel bakım gerektirebilen ve ağır seyreden semptomları nedeniyle hem toplumda hem de sağlık sisteminde krize yol açan bir hastalıktır. Bu nedenle enfekte insanların karantinaya alınması, taramaların arttırılması, sosyal mesafe sınırının korunması ve seyahat kısıtlılığı gibi önleyici tedbirler küresel boyutta uygulanmaya başlanmıştır (14)(15)(16).…”
Section: Introductionunclassified